Performance of nonlinear grading coating on polymeric outdoor insulators under lightning impulse voltages - Abd Rahman, Rahisham; Haddad, A.; Harid, Noureddine (2011)
This paper investigates the performance of an 11kV polymeric outdoor insulator equipped with a nonlinear grading material when subjected to a lightning impulse voltage. The grading layer is introduced as a field dependent material at the interface between the core and the silicone housing. The equipotential contours and electric field distribution over the insulator surface were computed and analysed using the Finite Element Method (FEM). Comparative studies show that the nonlinear grading layer, with an appropriate electrical property, can be an effective approach to reduce the electrical stress along the insulator by redistributing the surface field into a more uniform distribution.